VD_FINDINFO Jug / 2012 / 120 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
HOMICIDE PAR NÉGLIGENCE, DÉPENS, CAUSALITÉ ADÉQUATE, FAUTE DU TIERS, FAUTE PROPRE | 44 al. 1 CO, 117 CP, 59 LCR, 433 al. 1 CPP(CH), 433 al. 2 CPP (CH)